Entre a CasaGrande e o Borralho: as representações sociais sobre as trabalhadoras domésticas na novela Cheias de Charme - Santos, Rosana de Jesus dos (2018)
What social representations about domestic workers are conveyed in the soap opera Cheias de Charme? This question guides research. At the moment of voted the Law Project that changed the legislation sobre the domestic work in Brazil, the denominate PEC of the domestic workers, it was launched through the Rede Globo the soap opera "Cheias de Charme", proclaimed as the first display as the protagonist domestic workers. By means of the concept of Social Representation, such as, from Social Imaginary, were analyzed the meaning about domestic workers and domestic work conveyed in the soap opera. This was understood as a result of the current power relations in brazilian society at the time it was produced and disseminated, as well as bearer of meanings from other times in the history of the country. Its analysis therefore, allows anticipate continuities and / or transformations in the ways in which domestic workers and the domestic work have been signified by the said society. Issues related to domestic work are brushstrokes in the plot, whose emphasis is the meteoric rise of the three characters who form a trio of singers denominate “empreguetes”. Social differentiation, individualist social ascension and stardom are the lines that guide the plot, in which are reiterated, using the humor appeal, traditional representations about the domestic workers. These representations are permeated by constructions of gender, race, class and regional origin that are part of the process of subalternization that the domestic workers live in the country.